Prioritization of municipalities' strategies for sustainable income and financing resources - Eslambulchi, Alireza; Emami, Alireza; Jozei, Narges; Maroufi, Fakhradin (Revista Gestão & Tecnologia, 2018)
One of the most basic duties of strategist managers is foreseeing the future based on previous experiences and making a prediction in the moment in order to achieve future goals. Planning is a scheme of the past for making decisions in the moment corresponding to a future act. We cannot control the changes, but we can be prepared for them. On the other hand, considering the current intense economic fluctuations; resource limitation and price inefficiency of services in municipal organizations, determination of several various organizational duties and being autonomous and, variability of citizens' expectations and preferences in public goods have caused several problems for municipality managers in selecting sustainable income and financial resources. The present applied, structural and survey-based study provides a new conceptual model and makes use of indirect longitudinal observations over the timeline of 2011-2015 and the research data collected from 57 known elites including university instructors, experts, municipality managers and, members of the Islamic-council in addition to the application of the AHP method in order to explore, prioritize and select suitable strategies for securing municipalities' sustainable income and financial resources. Furthermore, research questions about the inequality of the competent main and subsidiary strategies' statuses in terms of strategic planning of sustainable income and financial resources of municipalities are elaborated on while prioritization of the former strategies for achieving the mentioned resources is completed using the Freedman test, student's t-test and, the AHP method in the SPSS software. The priorities of strategies for obtaining sustainable income and financial resources in the municipality of the city of Malayer include: amendment of the structure of municipalities' sustainable income and financial resources system as the 1st priority with an average weight of 0.2620; strategic management of sustainable income and financial resources as the 2nd priority with an average weight of 0.2249; amendment of the structure of the system of detection and collection of taxes as the 3rd priority with an average weight of 0.2146; participation of the private sector as the 4th priority with an average weight of 0.159 and; borrowing and grants as the 5th priority with an average weight of 0.0834.